Integrating water supply constraints into irrigated agricultural simulations of California. (October 2017) - Winter, Jonathan M.; Young, Charles A.; Mehta, Vishal K.; Ruane, Alex C.; Azarderakhsh, Marzieh; Davitt, Aaron; McDonald, Kyle; Haden, Van R.; Rosenzweig, Cynthia
Abstract: Simulations of irrigated croplands generally lack key interactions between water demand from plants and water supply from irrigation systems. We coupled the Water Evaluation and Planning system (WEAP) and Decision Support System for Agrotechnology Transfer (DSSAT) to link regional water supplies and management with field-level water demand and crop growth. WEAP-DSSAT was deployed and evaluated over Yolo County in California for corn, rice, and wheat. WEAP-DSSAT is able to reproduce the results of DSSAT under well-watered conditions and reasonably simulate observed mean yields, but has difficulty capturing yield interannual variability. Constraining irrigation supply to surface water alone reduces yields for all three crops during the 1987–1992 drought. Corn yields are reduced proportionally with water allocation, rice yield reductions are more binary based on sufficient water for flooding, and wheat yields are least sensitive to irrigation constraints as winter wheat is grown during the wet season. Highlights: We develop a coupled water planning and crop model for irrigated agriculture. We create an iterative approach to constrain water for irrigation based on supply. The model simulates corn, rice, and wheat reasonably well in California. We test the sensitivity of the model by limiting irrigation supply to surface water.